PVTx properties of binary mixed refrigerant R245fa/R152a for low temperature organic Rankine cycle. (May 2020) - Qi, Yingxia; Zhang, Fan; Yang, Haifeng; Liu, Yali; Niu, Shizhe; Zhang, Hua
Highlights: The mixed refrigerants (R245fa + R152a) as a new alternative ORC refrigerant. PVTx experimental data of (R245fa + R152a) mixtures at six mass fractions. Virial equations of state are fitted. Abstract: The gaseous PVTx properties of 1, 1, 1, 3, 3-pentafluoropropane (R245fa) + 1, 1-difluoroethane (R152a) mixtures are measured at temperatures from 305.20 K to 340.05 K at 5 K intervals, and pressures up to 0.8 MPa for mixture and the compositions of R245fa from 0.85 to 0.60 mass fraction using the Burnett isothermal expansion method. The uncertainties of experimental device is estimated to be within ±10 mK for temperature, ±4.0 kPa for pressure, ±0.3% for mass fraction, and ±0.06% for the composition factor. The experimental results are used to obtain tables of densities and compressibility factors for each mixture. And the second and third virial coefficients of gas virial EOS are fitted on the basis of experimental PVTx data. It provides a data reference for a further study of the R245fa/ R152a mixtures, which used low-temperature Organic Rankine Cycle.